Classical Circuit Theory - Wing, Omar.; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Classical Circuit Theory provides readers with the fundamental, analytic properties of linear circuits that are important to the design of conventional and non-conventional circuits in modern communication systems. These properties include the relations between phase and gain, between the real and imaginary parts, and between phase and group delay. They also include the fundamental limitations on gain and bandwidth, which are important in broadband matching in amplifier design. The idea that an impedance function is a positive real function and that a transfer function is bounded-real, forms the basis for analytic design of all conventional filters. At the same time, mathematical programming tools are now widely available so that design of non-conventional circuits by optimization is but a few mouse clicks away. Every new concept within the material is illustrated with one or more examples. There are exercises and problems at the end of the chapters. Some may be suitable for term projects. The design techniques presented are also illustrated step by step with easy-to-follow examples.
Fundamentals -- Circuit Dynamics -- Properties in the Frequency Domain -- The Impedance Function -- Synthesis of Two-Element-Kind Impedances -- Synthesis of RLC Impedances -- Scattering Matrix -- Synthesis of Transfer Functions -- Filter Design -- Circuit Design by Optimization -- All-Pass Circuits.
Keywords: Engineering; Electronics; Microelectronics; Electronic circuits; Engineering; Circuits and Systems; Electronics and Microelectronics, Instrumentation; Electronic books